2000
DOI: 10.1021/la991296t
|View full text |Cite
|
Sign up to set email alerts
|

Electroactive Myoglobin Films Grown Layer-by-Layer with Poly(styrenesulfonate) on Pyrolytic Graphite Electrodes

Abstract: Stable multilayer electroactive films were grown on rough pyrolytic graphite (PG) electrodes by alternate adsorption of layers of polyanion poly(styrenesulfonate) (PSS) and positively charged myoglobin (Mb) from their aqueous solutions. Incorporation of large amounts of electroactive Mb was facilitated by high electrode surface areas and by adsorbing coiled PSS from 0.5 M NaCl solutions. Cyclic voltammetry of {PSS/Mb}n films showed a pair of well-defined, chemically reversible peaks at about -0.25 V vs SCE at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
167
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(181 citation statements)
references
References 22 publications
12
167
2
Order By: Relevance
“…We base this on (1) the large difference in midpoint potential of a {Mb-PSS} n multilayer on pyrolitic graphite compared with that of Mb in solution, (2) the similar pH dependence of the midpoint potential of a {Mb-PSS} n multilayer on pyrolitic graphite and adsorbed heme, (3) the similar coverage of a {Mb-PSS} 6 multilayer on pyrolitic graphite and adsorbed heme (4) the similar peak separation of a {Mb-PSS} 6 multilayer and a PDDA-PSS-heme-PDDA-PSS film, (5) the high electron transfer rate constants of a {Mb-PSS} n multilayer, which is unlikely for electron transfer to protein molecules, but is in line with the electron transfer expected for a layer of adsorbed heme, (6) the fact that desorption of the multilayer induced by high pH does not result in the disappearance of the voltammetric peaks and (7) the fact that a large voltammetric response can be obtained by direct immersion in a Mb-PSS mixture, showing that the formation of multilayers is not necessary. Our conclusion is in apparent disagreement with previous studies on {Mb-PSS} n layer-by-layer films on pyrolitic graphite [22][23][24][25], in which it was concluded that Mb retains a near-native conformation in the layer-by-layer films. This was concluded mainly on the basis of spectroscopic data, which consistently show that Mb retains a near-native conformation.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We base this on (1) the large difference in midpoint potential of a {Mb-PSS} n multilayer on pyrolitic graphite compared with that of Mb in solution, (2) the similar pH dependence of the midpoint potential of a {Mb-PSS} n multilayer on pyrolitic graphite and adsorbed heme, (3) the similar coverage of a {Mb-PSS} 6 multilayer on pyrolitic graphite and adsorbed heme (4) the similar peak separation of a {Mb-PSS} 6 multilayer and a PDDA-PSS-heme-PDDA-PSS film, (5) the high electron transfer rate constants of a {Mb-PSS} n multilayer, which is unlikely for electron transfer to protein molecules, but is in line with the electron transfer expected for a layer of adsorbed heme, (6) the fact that desorption of the multilayer induced by high pH does not result in the disappearance of the voltammetric peaks and (7) the fact that a large voltammetric response can be obtained by direct immersion in a Mb-PSS mixture, showing that the formation of multilayers is not necessary. Our conclusion is in apparent disagreement with previous studies on {Mb-PSS} n layer-by-layer films on pyrolitic graphite [22][23][24][25], in which it was concluded that Mb retains a near-native conformation in the layer-by-layer films. This was concluded mainly on the basis of spectroscopic data, which consistently show that Mb retains a near-native conformation.…”
Section: Discussioncontrasting
confidence: 99%
“…The midpoint potential is -0.04 ± 0.01 V versus SHE and the peak separation is 120 ± 10 mV. All these properties are in reasonable agreement with results in the literature [24] and show that we have prepared similar films.…”
Section: Preparation Of a Pdda-pss-heme-pdda-pss Layer On Pyrolitic Gsupporting
confidence: 91%
See 1 more Smart Citation
“…The˛n was calculated to be 0.52. Given 0.3 <˛< 0.7 in general (Ma et al, 2000), it could be concluded that n = 1 and˛= 0.52. So, the redox reaction between HRP and the NAE was a single electron transfer process.…”
Section: Direct Electron Transfer Of Hrp On the Gold Nanowire Array Ementioning
confidence: 99%
“…The value of the slope (-61.5 mV·pH -1 ) was close to that expected theoretically -59 mV·pH -1 for a one-electron oneproton reaction, indicating that a single proton transfer accompanied in the electrochemical process of Hb. The electrochemical reduction of Hb could be simply expressed as follows: 38 Hb heme Fe(III) + H + + e -« Hb heme Fe(II)…”
Section: Effect Of Ph Valuementioning
confidence: 99%